Labor Force Problems In Some Industrial Companies In Basra ProvincThe state company of Southern Fertilizer , The General Company for Petrochemical Industries As A Sampl - Abd AlQader Al Ramdan , Lect . Sudus (Basra studies journal, 2026)
The labor force is one of the fundamental components of industrial development which can only be achieved by developing the skills of workers providing all types of health , cultural services and a suitable work environment for them. The research aims at examining a set of problems facing the labor force at The state company of Southern Fertilize and The General Company for Petrochemical Industries in the Governorate of Bara for the year 2024.In order to improve and increase productivity by raising performance levels, reducing the wasted time, and optimizing workforce utilization, as well as identifying skills and social status in order to provide suitable housing and services to alleviate psychological stress that affects worker productivity. .A questionnaire form was distributed randomly, with100 forms for each company. 200 forms were collected, all of which were filled out by the labor force in both companies. The study addressed several problems facing the labor force. It concluded by presenting a set of recommendations like: increasing wages in line with the nature of the work, providing a suitable residential environment that meets all the necessary health requirements for living, and other proposals that serve the worker.